1978
DOI: 10.1037/0033-2909.85.3.618
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements in reading and information processing.

Abstract: Recent studies of eye movements in reading and other information processing tasks, such as music reading, typing, visual search, and scene perception, are reviewed. The major emphasis of the review is on reading as a specific example of cognitive processing. Basic topics discussed with respect to reading are (a) the characteristics of eye movements, (b) the perceptual span, (c) integration of information across saccades, (d) eye movement control, and (e) individual differences (including dyslexia). Similar top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
536
1
20

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 915 publications
(577 citation statements)
references
References 275 publications
(341 reference statements)
20
536
1
20
Order By: Relevance
“…Characteristics of the writing system also influence eye movements (Osaka, 1989;Peng, Orchard, & Stem, 1983;Sun, Morita, & Stark, 1985). A crucial point that has emerged recently is that eye movement measures can be used to infer moment-to-moment cognitive processes in reading (Just & Carpenter, 1980;McConkie, Hogaboam, Wolverton, Zola, & Lucas, 1979;Rayner, 1978b;Rayner, Sereno, Morris, Schmauder, & Clifton, 1989) and that the variability in the measures reflects on-line processing. For example, there is now abufidant evidence that the frequency of a fixated word influences how long readers look at the word (Inhoff 8~ Rayner, 1986;Rayner & Duffy, 1986).…”
Section: Eye Movements In Readingmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the writing system also influence eye movements (Osaka, 1989;Peng, Orchard, & Stem, 1983;Sun, Morita, & Stark, 1985). A crucial point that has emerged recently is that eye movement measures can be used to infer moment-to-moment cognitive processes in reading (Just & Carpenter, 1980;McConkie, Hogaboam, Wolverton, Zola, & Lucas, 1979;Rayner, 1978b;Rayner, Sereno, Morris, Schmauder, & Clifton, 1989) and that the variability in the measures reflects on-line processing. For example, there is now abufidant evidence that the frequency of a fixated word influences how long readers look at the word (Inhoff 8~ Rayner, 1986;Rayner & Duffy, 1986).…”
Section: Eye Movements In Readingmentioning
confidence: 99%
“…Many different techniques have been used to estimate the size of the effective visual field or perceptual span in reading. However, most of them have severe limitations that are not discussed here (see Rayner, 1975bRayner, , 1978b for discussion). Rather, the focus is on studies using eye-contingent display tech-4 Ishida and Ikeda (1989) concluded that the visual sensitivity that is suppressed during a saccade recovers only partially during the initial part of a fixation and that it is fully recovered approximately 70 ms after the beginning of the fixation.…”
Section: The Perceptual Span In Readingmentioning
confidence: 99%
“…Certainly some of these principles are not new (see, e.g., Engbert et al, 2002;Inhoff et al, 2000a;Kennedy et al, 2002;Kolers, 1976;Rayner, 1978). Indeed, they combine into a model that could be tabulated under the heading of "mixed models" by Rayner (1978, …”
Section: A Principled Account Of Eye-movement Control In Readingmentioning
confidence: 99%
“…Indeed, they combine into a model that could be tabulated under the heading of "mixed models" by Rayner (1978, …”
Section: A Principled Account Of Eye-movement Control In Readingmentioning
confidence: 99%
See 1 more Smart Citation